Synthesis and Characterization of Monolayer Colloidal Sheets - Daware, Santosh Vasant (Langmuir : the ACS journal of surfaces and colloids, 2024)
Sheet-like colloidal assemblies represent model systems to investigate the structure and properties of two-dimensional materials. Here, we report a simple yet versatile method for the preparation of colloidal monolayer sheet-like assemblies that affords control over the size, crystalline order, flexibility, and defect density. The protocol that we report relies on self-assembly of colloids as a sessile drop of dispersion is evaporated on an oil-covered substrate. In this case, the contact line continually moves as the drop shrinks. Polyethyleneimine polymer-covered micrometer-sized colloidal particles are transported to the air-water interface and assemble to form a monolayer sheet as the drop dries. Cross-linking the polymer renders the colloidal assembly permanent. Interestingly, monodisperse colloidal particles form disordered assemblies when dried from low concentration dispersions, while polycrystalline ordered assemblies form at higher concentrations. We demonstrate that increasing the cross-linker to polymer ratio decreases the flexibility of the assembly. Introduction of different-sized colloidal particles in a sheet leads to increased disorder. Removal of sacrificial particles from the sheet allowed the introduction of "holes" in the sheets. Thus, these colloidal sheets are models for probing the effects of disorder, doping, and vacancies in two-dimensional systems